VO2Max Capacity Level Survey for Futsal Extracurricular Students - Akbar Sudirman (East Asian Journal of Multidisciplinary Research, 2022)
This study aims to determine the VO2Max capacity of futsal extracurricular students at SMKN 10 Makassar. Through this research, the coach or trainer can directly find out the vo2max capacity of the athlete, so that they have basic guidelines for developing an exercise program. The variable in this study is the independent variable, namely the student's vo2max capacity. The research method uses a quantitative approach by conducting direct tests using the 20 metters bleep test instrument, the sample in this study was male students participating in extracurricular futsal at SMKN 10 Makassar totaling 20 people with varying age categories from 15-18 years. This research can be completed 1 face-to-face. Based on the results of the study, the average VO2Max prediction value for futsal extracurricular students at SMKN 10 Makassar was 42.11 ml/kg/min. Based on the VO2Max table, the average VO2Max prediction value for futsal extracurricular students at SMKN 10 Makassar is in the sufficient category.